HUKUM NIKAH MUT’AH MENURUT TEKSTUAL DAN KONTEKSTUAL - Santoso, Rudi (El-Izdiwaj: Indonesian Journal of Civil and Islamic Family Law, 2020)
Mut 'ah marriage has been a controversial model of marriage and its validity is still a debate between sunnis and Syiah down to this day.The study is classified in the library or library research that USES the judicial approach method.The study concluded that there was no fuqaha difference of opinion among Ahlu Sunnah and Shia about the mut 'marriage performance during the time of god's messenger PBUH. But then mut 'ah's marriage became an effort among them. According to fuqaha ahluu sunnah that mut's marriage is a illegitimate law (haram) in the era after the prophet has until now even until the end of days, just as the prophet has kept him for six different occasions.While fuqaha shia shi 'ah imamiyah allows mut'ah marriage on the ground that there is not a single verse that does not forbid mut 'ah marriage and is fine men out of the safar state, however well as the muqim, and mut 'ah marriage laws are still legal. Although in recent times, some peoples of the Shia would gave opinion, not all those halal must be executed.